Emergent craniotomy in rural and regional settings – recommendations from a tertiary neurosurgery unit: surgical technique and future prospects. Issue 5 (17th January 2022) - Raman, Vignesh; Jiwrajka, Manasi; Pollard, Cliff; Grieve, David A; Alexander, Hamish; Redmond, Michael
Abstract: Kenneth G Jamieson described the emergent craniotomy for traumatic brain injuries (TBI) in the rural and regional setting back in 1965 in his book 'A First Notebook Of Head Injury'. Since then, there has been successful use of the technique in peripheral hospitals prior to the safe transfer of patients to metropolitan trauma centres. Although the procedure can be daunting in inexperienced hands, our institution supports ongoing education to continue implementation of trauma craniotomies by non‐neurosurgeons if it means another life is potentially saved. Here we describe the surgical technique for an emergent craniotomy and craniectomy. Although the surgical technique has been described elsewhere, we have done so in a simplified 10‐step approach with consideration of available resources in the peripheral hospital setting and the added pearls from the experience of a metropolitan neurosurgical unit. We also discuss future prospects for undertaking neurosurgical operations in peripheral hospitals but with intra‐operative tele‐surgery monitoring and supervision. Abstract : How to perform an emergent craniotomy in the rural and regional setting for life‐threatening traumatic brain injuries.